2020
DOI: 10.1159/000510727
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography-Angiography in Geographic Atrophy

Abstract: Geographic atrophy (GA) represents the non-exudative late stage of age-related macular degeneration and constitutes a leading cause of legal blindness in the developed world. It is characterized by areas of loss of outer retinal layers including photoreceptors, degeneration of the retinal pigment epithelium, and rarefication of the choriocapillaris. As all three layers are functionally connected, the precise temporal sequence and relative contribution of these layers towards the development and progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…High blood pressure is shown to be associated with lower choroidal blood flow and disturbed vascular homeostasis [ 30 ]. Since perfusion deficits in the choriocapillaris, the innermost layer of the choroid, are associated with future GA progression [ 31 ], an associate between hypertension and increased GA progression appears biologically plausible. Regarding the association of hypercholesterinemia and decreased GA progression, the biological plausibility remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…High blood pressure is shown to be associated with lower choroidal blood flow and disturbed vascular homeostasis [ 30 ]. Since perfusion deficits in the choriocapillaris, the innermost layer of the choroid, are associated with future GA progression [ 31 ], an associate between hypertension and increased GA progression appears biologically plausible. Regarding the association of hypercholesterinemia and decreased GA progression, the biological plausibility remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Cicinelli et al [31] used OCTA to observe hyaline warts and choroidal capillaries, and concluded that OCTA can detect insufficient choroidal vascular perfusion to identify hyaline warts and diagnose choroidal capillary dysfunction. Geographic atrophy (GA) is a typical characteristic change in late stage dry AMD [32]. OCTA shows a significant decrease in capillary signal within the GA lesion, while the signal in the surrounding area is normal.…”
Section: Application Of Octa In Dry Amdmentioning
confidence: 99%
“…Each B scan repeated the OCT angiogram at the same position at least twice. Furthermore, OCTA was performed with the Supervisory Control And Data Acquisition (SSADA) algorithm [10] with a working wavelength of 840 nm and 7000 axial scans per second. After scanning the retinal and choroidal vessels, OCTA can be divided into four layers: the superficial and deep retinal plexus, the outer retina and the choriocapillaris.…”
Section: Octa Examinationmentioning
confidence: 99%
“…Optical coherence tomography angiography (OCTA) is a newly developed technique for fundus examination. In contrast with traditional examinations, this technique does not require the injection of contrast agents; it also has included a wider array of indicators, a better safety profile and can provide quantitative data relating to ocular blood flow [8][9][10]. In this study, we investigated the relationship between sex hormone levels and OCTA parameters in male CSC patients in attempt to identify factors involved in the pathogenesis of CSC.…”
Section: Introductionmentioning
confidence: 99%